DATA-DRIVEN PUBLIC GOVERNANCE AND THE LEGAL LIMITS OF THE USE OF ARTIFICIAL INTELLIGENCE IN PUBLIC ADMINISTRATION (Interdisciplinary Studies Journal, 2026)
The advancement of digital transformation in Public Administration has intensified the use of artificial intelligence and Big Data technologies in the formulation, implementation, and evaluation of public policies. This movement is part of the context of data-driven public governance, which seeks to enhance administrative efficiency, rationality in decision-making, and the State’s capacity to respond to complex social demands. However, the incorporation of these technologies raises significant legal challenges, especially with regard to the compatibility between automated decisions and the structuring principles of Administrative Law. In light of this scenario, this article examines the legal limits of the use of artificial intelligence in Brazilian Public Administration, focusing on the principles of legality, transparency, reasoning of administrative acts, and institutional oversight. The research adopts a qualitative, theoretical-dogmatic approach, based on a literature review and normative analysis, examining how algorithmic opacity, automated decision-making, and the intensive use of data may place pressure on fundamental guarantees and traditional oversight mechanisms. It is concluded that, although data-driven governance represents an important opportunity for improving public management, its legal legitimacy depends on strict compliance with administrative principles, the adoption of mechanisms for algorithmic explainability, and the strengthening of oversight bodies, in order to ensure public decisions that are transparent, accountable, and compatible with the Democratic Rule of Law.
Keywords: Public Governance; Artificial Intelligence; Big Data; Public Administration; Administrative Control